USE 3D-models in multimedia electronic educational resources - Мелешко, М. А.; Денисенко, С. М.; Пясківський, М. І. (Problems of Informatization and Control, 2015)
Relevance of the article due to the need to reform higher education in accordance with the growing demands of the modern information society. One of the goals of this process is the use in the professional training of students new learning tools - electronic multimedia educational resources. Submitted feature of use multimedia educational resources in the university, including  such their component  as 3D-model. Examples are given of the multimedia resource, including demonstration educational  of 3D-models